Pengaruh Iklan Instagram Stories terhadap Keputusan Pembelian Mahasiswa Politeknik Negeri Bandung - Slamet, Ditabi Pera (International Journal Administration, Business & Organization, 2023)
The purpose of this study was to determine the effect of Instagram stories advertisements on the purchasing decisions of Bandung State Polytechnic students. The sample used in this study was 110 Instagram user respondents. This study uses a quantitative descriptive method with data analysis methods in the form of validity tests, reliability tests, correlation analysis, and simple regression analysis. The data collection technique uses a media questionnaire that is distributed through social media and directly face-to-face. In this study, the results obtained were 43.4% of the influence of Instagram stories advertisements on the purchasing decisions of Bandung State Polytechnic students, while 56.6% of the purchasing decisions of Bandung State Polytechnic students were influenced by other variables not tested in this study. The results of this study indicate that Instagram stories advertisements influence the purchasing decisions of Bandung State Polytechnic students, but the effect is included in the low criteria.